Liposomal Antioxidants for Protection against Oxidant-Induced Damage - Zacharias E. Suntres (Journal of Toxicology)
Reactive oxygen species (ROS), including superoxide anion, hydrogen peroxide, and hydroxyl radical, can be formed as normal products of aerobic metabolism and can be produced at elevated rates under pathophysiological conditions. Overproduction and/or insufficient removal of ROS result in significant damage to cell structure and functions. In vitro studies showed that antioxidants, when applied directly and at relatively high concentrations to cellular systems, are effective in conferring protection against the damaging actions of ROS, but results from animal and human studies showed that several antioxidants provide only modest benefit and even possible harm. Antioxidants have yet to be rendered into reliable and safe therapies because of their poor solubility, inability to cross membrane barriers, extensive first-pass metabolism, and rapid clearance from cells. There is considerable interest towards the development of drug-delivery systems that would result in the selective delivery of antioxidants to tissues in sufficient concentrations to ameliorate oxidant-induced tissue injuries. Liposomes are biocompatible, biodegradable, and nontoxic artificial phospholipid vesicles that offer the possibility of carrying hydrophilic, hydrophobic, and amphiphilic molecules. This paper focus on the use of liposomes for the delivery of antioxidants in the prevention or treatment of pathological conditions related to oxidative stress.